PENGEMBANGAN PROTOKOL PENGKAJIAN SIRKULASI KAKI PADA PASIEN DIABETES MELITUS - Azhar, Bayu; Suza, Dewi Elizadiani; Ariani, Yesi (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2019)
Kaki diabetik merupakan komplikasi akibat gangguan sirkulasi dan neuropati. Pasien diabetes melitus memiliki resiko mengalami gangguan penyakit arteri perifer merupakan komplikasi makrovaskuler dan mikrovaskuler mengakibatkan terganggunya sirkulasi pembuluh darah. Diagnostik awal dapat melakukan pemeriksaan pengkajian sirkulasi kaki pasien diabetes. Tujuan penelitian yaitu pengembangan protokol pengkajian sirkulasi kaki pasien diabetes mellitus. Desain penelitian menggunakan action reseach yang dilakukan satu siklus di Rumah Sakit Umum Mitra Medika Tanjung Mulia Medan, dengan teknik purposive sampling. Instrumen penelitian in-depth interview, focus grup discussion, kuesioner pengetahuan perawat tentang pengkajian sirkulasi kaki pasien diabetes melitus. Partisipan terdiri dari 45 perawat ruangan. Hasil penelitian menghasilkan 4 tema: 1) Strategi penerapan protokol pengkajian sirkulasi kaki pasien diabetes melitus, 2) Manfaat dalam penerapan protokol pengkajian sirkulasi kaki pasien diabetes melitus, 3) Hambatan dalam penerapan protokol pengkajian sirkulasi kaki pasien diabetes melitus, dan 4) Teknik dan penerapan protokol pengkajian sirkulasi kaki pasien diabetes melitus. Hasil analisis kuantitatif tingkat pengetahuan perawat sebelum kegiatan penelitian 86,66%, dan meningkat menjadi 100% setelah kegiatan penelitian. Direkomendasikan pelaksanaan pengkajian sirkulasi kaki pasien diabetes melitus sesuai standar prosedur sehingga dapat mengidentifikasi sirkulasi kaki pasien diabetes melitus, memperbaiki kualitas pelayanan keperawatan, meningkatkan kompetensi perawat. Kata kunci: Protokol, pengkajian sirkulasi kaki, diabetes melitus Abstract Development of protocol assessment of feet circulation in diabetes melitus patients. Diabetic foot is complication caused by circulation disorder and neuropathy in patients who have the risk for peripheral artery disease which is the complication of macro-vascular and micro-vascular which can eventually cause the incidence of circulation disorder in blood vessels. Initial diagnostic can be done to prevent peripheral artery disease by using circulation studying examination on the feet of diabetic patients. Therefore, it’s necessary to develop studying protocol of foot circulation in diabetes mellitus patients at Mitra Medika Hospital, Medan. The research instrument was interviews, in-depth interviews, guidance for focus group discussion, self-report of nurses’ knowledge of studying on foot circulation diabetic patients. Participants from 45 nurse practitioners, taken by using purposive sampling technique. The data were analyzed qualitatively and quantitatively. Qualitative data were analyzed by using content analysis while quantitative data were analyzed by using descriptive statistic test. The result of the research showed that 4 themes: 1) strategy of implementing studying protocol of foot circulation diabetes mellitus patients, 2) the benefit of studying protocol of foot circulation diabetes mellitus patients, 3) obstacles in studying protocol of foot circulation diabetes mellitus patients, and 4) technique and implementation of studying protocol of foot circulation diabetes mellitus patients. The result of quantitative analysis showed that nurses’ knowledge in pre-research of was 86.66% and increased to 100% in post research activity. The output of this research result was the standard of studying foot circulation diabetes mellitus patients. It’s recommended the implementation of studying foot circulation accordance with the standard of procedure so that it can identify diabetes mellitus patients’ foot circulation, nursing care quality should be improved, and nurses’ competence should be increased. Keywords: protocol, assessment of foot circulation, diabetes mellitus